Impacto del periodismo ambiental en las relaciones interculturales de las mujeres temporeras en la Tabacalera Francey del cantón El Empalme año 2022 - Davila Loor, Keyla Andreina (2022)
Communication on sustainability, a combination of communication for development and environmental communication, has grown significantly over the last decade, especially driven by international environmental organizations. To analyze the contextual information in digital media, descriptive and content analysis studies are carried out, where seasonal women in the Francey tobacco company in El Empalme canton were examined; with an analysis of (Banegas, Olivares, Terceros, & Hidalgo, 2011) environmental information from (Arias, 2011) for the digital medium. The types of news (traditional and online news) are classified, hypertext, updates, information sources, sources, topics, comments and terminology are explained. The importance of communication for sustainable development is beyond any doubt when the need to change the prevailing development paradigm is recognized so that the global environmental crisis that also affects Latin American countries does not continue to deepen. In recent decades, environmental issues have gone from a marginal position to a prominent place on the world agenda due to their importance in the development process and their impact on the life and future of humanity. It was concluded that the content that all cultures change with the needs of changing circumstances.